The varieties of grounded theory - Bryant, Antony (London : SAGE Publications Ltd, 2019)
The Varieties of Grounded Theory explores the range and depth of grounded theory methodology, and the ways in which discussions in the field have developed and expanded in recent years. In this SAGE Swift, Anthony Bryant provides a jargon-free overview of grounded theory terminology, whilst examining the impact of recent technological and theoretical advances on how it is currently practiced. Increasingly popular outside of its original settings, grounded theory is now a core method for business & management, criminology, politics, geography and psychology. This book provides a global interdisciplinary perspective on the method's utility today, and complements The SAGE Handbook of Current Developments in Grounded Theory (April 2019).
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Grounded theory -- Methodology